Effect of Apacharama bark ashes on the physical-mechanical properties of solid brick - Ramírez Aquino, Marco (2023)
The growing interest in finding sustainable alternatives in the construction industry and brick manufacturing process has promoted the efficient reuse of sources such as ashes from various materials. Therefore, the study aimed to determine the effect of Apacharama bark ashes (ABA) on the physical-mechanical properties of solid bricks. The study sample for the tests consisted of 72 units, with varying percentages of ABA addition (5 %, 7.5 %, and 10 %). Physical and mechanical properties, such as water absorption, warping, and axial compressive strength (per unit, stack, and wall), and diagonal compressive strength (wall), were analyzed. The test results revealed that the addition of 10 % ABA improves both axial and diagonal compressive strength. An increase in water absorption percentage at 28 days was also observed, even though it exceeded established standards. However, warping behavior remained within acceptable limits. These findings were possibly favored in part by chemical composition. Hence, there is a need to optimize the addition percentages to balance properties without compromising other characteristics.